2018
DOI: 10.3390/brainsci8060105
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Self-Esteem in White and Black Older Adults in the United States

Abstract: Background. Poor self-esteem is a core element of depression. According to recent research, some racial groups may vary in the magnitude of the link between depression and poor self-esteem. Using a national sample, we compared Black and White older Americans for the effect of baseline depressive symptoms on decline in self-esteem over time. Methods. This longitudinal study used data from the Religion, Aging, and Health Survey, 2001–2004. The study followed 1493 older adults (734 Black and 759 White) 65 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 95 publications
0
5
0
2
Order By: Relevance
“…A recent review discussed the differences between Blacks and Whites in social, emotional, and cognitive correlates of depression [ 48 ]. Some studies showed Blacks who are depressed maintain higher levels of overall sense of mastery and hope, which may reduce their suicidality [ 37 , 38 , 49 , 50 , 51 ]. However, higher education may not be as protective for Blacks as it is for Whites [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review discussed the differences between Blacks and Whites in social, emotional, and cognitive correlates of depression [ 48 ]. Some studies showed Blacks who are depressed maintain higher levels of overall sense of mastery and hope, which may reduce their suicidality [ 37 , 38 , 49 , 50 , 51 ]. However, higher education may not be as protective for Blacks as it is for Whites [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blacks demonstrate systemic resilience despite all the stressors [51,52]. Blacks report higher levels of optimism and hope than Whites under adversities [19,20,121,122]. This pattern is in contrast to the cumulative or multiple adversity hypotheses, that conceptualize Blacks and other minority groups as vulnerable groups [123].…”
Section: Discussionmentioning
confidence: 99%
“…Blacks use social support [118,135,136] and religion [135,137] to maintain a high level of mental well-being. They also maintain hope and positive emotions as well as a sense of mastery even in the presence of negative emotions and depression [19,20,121,122]. Keyes has discussed the “Black advantage” in mental health, possibly due to flourishing in response to adversity [138].…”
Section: Discussionmentioning
confidence: 99%
“…Blacks and Whites also differ in the effect of stress on chronic disease and depression, possibly due to their differential behavioral coping strategies (82)(83)(84)(85)(86). Moderating effects of context, race, and ethnicity holds for a wide range of psychosocial domains and health (26,27,77,78). This is in part because race, ethnicity and culture shape experiences and expression of emotions (87,89).…”
Section: Discussionmentioning
confidence: 99%